Pelembab Kulit Alami Dari Sari Buah Jeruk Bali [Citrus maxima (Burm.) Osbeck] - Ervina Syahfitri Lubis; Lely Sari Lubis*; Julia Reveny (Journal of Pharmaceutics and Pharmacology, 2012)
Background: Pomelo fruit contains antioxidants such as lycopene, flavonoids, provitamin A and vitamin C are very good in scavenging free radicals. In addition, pomelo that contains pectin, vitamins B1, B2, folic acid, energy, water, sugar, protein, fat, carbohydrate, retinol, calcium and phosphorus. Sugar in pomelo able to bind water in the air so to reduce the evaporation of water in the skin. Moisture levels will be maintained and will not be dehydrated and skin becomes dry. Objective: To make cream using natural moisturizing ingredients contained in pomelo. Methods: Pomelo juice was dried with freeze dryer to obtain a concentrated juice, and then formulated into a cream in six formula: fruit juice concentration 2.5, 5, 7.5, 10%, a cream containing 2% glycerin and cream without sample (blank). Tests conducted include: test of homogeneity, stability observations, test pH, emulsion type test, the skin irritation test on volunteers and the ability of the preparation to reduce the evaporation of water from the skin with moisture binding method of skin by the silica gel. Results: The results showed that the preparations were homogeneous and stable during 12 weeks of storage, except at a concentration of 10% fruit juice. The preparation had a pH of 6.2 to 6.8, an emulsion type O/W, did not irritate skin and did not cause rough. The results of testing the ability of reduction of water evaporation from the skin showed that the higher concentration of pomelo juice on the cream, the greater ability to reduce water evaporation from the skin. Conclusion: Pomelo juice at concentration 7.5% in cream can be used as a natural skin moisturizer. Keywords: pomelo juice, Citrus maxima (Burm.) Osbeck, cream, skin moisturizer ABSTRAK Latar belakang: Buah jeruk bali mengandung antioksidan seperti likopen, flavonoid, provitamin A dan vitamin C yang sangat baik dalam menangkal radikal bebas. Selain itu, buah jeruk bali juga mengandung pektin, vitamin B1, B2, asam folat, energi, air, gula, protein, lemak, karbohidrat, retinol, kalsium dan fosfor. Kandungan gula dalam jeruk bali mampu mengikat air di udara sehingga dapat mengurangi penguapan air di kulit. Kelembapan kulit akan terjaga dan kulit tidak akan dehidrasi dan menjadi kering. Tujuan: Membuat krim dengan memanfaatkan bahan pelembab alami yang terkandung dalam buah jeruk bali. Metode: Sari buah jeruk bali dikeringkan dengan freeze dryer sehingga diperoleh sari kental, kemudian diformulasikan menjadi krim dalam 6 formula yaitu: konsentrasi sari buah 2,5; 5; 7,5; 10%, krim yang mengandung gliserin 2% dan krim tanpa sampel (blanko). Pengujian yang dilakukan antara lain: uji homogenitas, pengamatan stabilitas, uji pH, uji tipe emulsi, uji iritasi terhadap kulit pada sukarelawan dan kemampuan sediaan untuk mengurangi penguapan air dari kulit dengan metode pengikatan uap air dari kulit oleh silika gel. Hasil: Hasil penelitian menunjukkan bahwa sediaan homogen dan stabil selama penyimpanan 12 minggu, kecuali pada konsentrasi sari buah 10%. Sediaan krim mempunyai pH 6,2-6,8, merupakan tipe emulsi m/a, tidak mengiritasi dan tidak menyebabkan kulit kasar. Hasil pengujian kemampuan pengurangan penguapan air dari kulit menunjukkan bahwa semakin tinggi konsentrasi sari buah jeruk bali pada sediaan krim maka semakin besar kemampuan sediaan krim untuk mengurangi penguapan air dari kulit. Kesimpulan: Sari buah jeruk bali dengan konsentrasi 7,5% pada krim dapat digunakan sebagai bahan pelembab alami kulit. Kata kunci : sari buah jeruk bali, Citrus maxima (Burm.) Osbeck, krim, pelembab kulit